Influences of cooking and storage on γ-aminobutyric acid (GABA) content and distribution in mung bean and its noodle products. (15th January 2022) - Ma, Yuling; Wang, Aixia; Yang, Mei; Wang, Shanshan; Wang, Lili; Zhou, Sumei; Blecker, Christophe
Abstract: The γ-aminobutyric acid (GABA) content and distribution of mung bean (MB), heat and relative humidity treated MB (HRH-MB) under different cooking and storage conditions were investigated. The quality characteristics of noodles prepared by MB and HRH-MB were evaluated. Results showed that black MB varieties presented a higher average GABA content under HRH treatment than that of green MB varieties. Soaking significantly increased the GABA content of MB (P < 0.05), but, 58.78% of GABA in HRH-MB were distributed in the soaking solution. After cooking, although the GABA of HRH-MB had a slightly degradation, its content was higher than MB. With the increase of storage time, the GABA content in MB increased initially, followed by a decrease, whereas a slower reduction was observed on HRH-MB. Besides, compared with the mixed MB-wheat flour and noodles, the pasting properties of mixed HRH-MB-wheat flour, the color and texture properties of mixed HRH-MB-wheat noodles were improved and closer to wheat flour and noodles, respectively. Furthermore, the mixed HRH-MB-wheat noodles exhibited the highest GABA content (16.56 mg/100 g DW) after cooking. Therefore, HRH-MB may be an ideal material for enhancing GABA and improving the quality characteristic of MB-based foods. Highlights: Heat and relative humidity (HRH) enhanced γ-aminobutyric acid content of mung bean. For mung bean, soaking largely increased its γ-aminobutyric acid content. For HRH-mung bean, most of γ-aminobutyric acid was dissolved in the soaking solution. γ-aminobutyric acid in HRH-mung bean was slightly degraded after cooking and storage. HRH-mung bean noodles had the highest γ-aminobutyric acid content.